A Nb-doped metal hydride electrode with overcharge resistance and wide temperature performance for aqueous rechargeable batteries. (September 2022) - Tan, Cheng; Ouyang, Liuzhang; Min, De; Liao, Canhui; Zhu, Min
Abstract: Metal hydride electrodes have been widely used for aqueous rechargeable batteries with good wide temperature performance compared to lithium-ion batteries. For the first time, the design and application of Nb-doped metal hydride electrode with excellent overcharge resistance in this study for La0.46 Ce0.42-x Pr0.03 Nd0.08 Zr0.02 Nbx Ni4.41 Mn0.36 Al0.28 ( x = 0, 0.05 or 0.1). The ratio of capacity retention after the 100th cycle for charging 420 and 360 mAh g −1 increases from 86.99% ( x = 0) to 99.93% ( x = 0.1) at 25 °C, and from 83.95% ( x = 0) to 99.28% for ( x = 0.1) at 50 °C. Furthermore, the capacity of simulated wide temperature and overcharge experiment at -20 °C increases from 86.3 mAh g −1 ( x = 0) to 217.8 mAh g −1 ( x = 0.1) after the 100th cycle at 50 °C, due to the increase of overcharge resistance. This material makes it a promising candidate as electrode material for wide temperature applications. Graphical abstract: Image, graphical abstract .